2015 IEEE Symposium on Security and Privacy 2015
DOI: 10.1109/sp.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

SoK: Research Perspectives and Challenges for Bitcoin and Cryptocurrencies

Abstract: Bitcoin has emerged as the most successful cryptographic currency in history. Within two years of its quiet launch in 2009, Bitcoin grew to comprise billions of dollars of economic value despite only cursory analysis of the system's design. Since then a growing literature has identified hidden-but-important properties of the system, discovered attacks, proposed promising alternatives, and singled out difficult future challenges. Meanwhile a large and vibrant open-source community has proposed and deployed nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
580
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 906 publications
(640 citation statements)
references
References 59 publications
0
580
0
9
Order By: Relevance
“…Neither the payers nor the payees in any transactions should be identified in the public record. Although Bitcoin's strong user privacy is claimed in the original paper of Bitcoin [51], many previous studies have demonstrated that it is still possible to cluster Bitcoin addresses belonging to the same user by conducting transaction graph analysis, and further link these addresses to online merchants because some of their addresses are publicly known [27]. Nevertheless, it is still considered impossible to de-anonymize arbitrary Bitcoin users [49].…”
Section: ) Linking Bitcoin Addresses To Ios Devicesmentioning
confidence: 99%
“…Neither the payers nor the payees in any transactions should be identified in the public record. Although Bitcoin's strong user privacy is claimed in the original paper of Bitcoin [51], many previous studies have demonstrated that it is still possible to cluster Bitcoin addresses belonging to the same user by conducting transaction graph analysis, and further link these addresses to online merchants because some of their addresses are publicly known [27]. Nevertheless, it is still considered impossible to de-anonymize arbitrary Bitcoin users [49].…”
Section: ) Linking Bitcoin Addresses To Ios Devicesmentioning
confidence: 99%
“…The next step is to apply the parameters and design the contract. We already have the test ethers so the contract can be made and system will charge some of the ethers [7]. One thing you have to keep in mind and that is more is the charge, faster will be your transaction.…”
Section: Deployment Of Codementioning
confidence: 99%
“…Moreover, since the blockchain has an openness attribute, it can provide transparency in data when applied to an area requiring the disclosure of data. Due to such strengths, it can be utilized in diverse areas including the financial sector and the Internet of Things (IoT) environment and its applications are expected to expand [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%